Simple two‐dimensional ultrasound technique to assess intrapartum cervical dilatation: a pilot study. (25th March 2013) - Hassan, W. A.; Eggebø, T. M.; Ferguson, M.; Lees, C.
ABSTRACT Objectives To describe a two‐dimensional (2D) ultrasound technique to measure cervical dilatation in labor, and to compare ultrasound with digital measurements. Methods 2D transperineal ultrasound was performed in 21 nulliparous women in labor with a singleton fetus in cephalic presentation and cervical dilatation measured before or after a digital vaginal examination. The absolute difference was calculated and Bland–Altman analysis was used to assess the mean difference between digital vaginal examination and ultrasound examination of cervical dilatation. Pearson analysis was used to determine the correlation between digital and ultrasound measurements. Intraclass correlation coefficients (ICCs) with 95% CI were used to evaluate the reliability of the two methods. Results Satisfactory quality images of the cervix were obtained in 19 of 21 cases. There was positive correlation between 2D ultrasound measurement of cervical dilatation and digital vaginal examination (Pearson coefficient r = 0.821, n = 19, P < 0.001). Bland–Altman analysis showed a mean difference between digital and ultrasound measurements of 0.08 cm (95% limits of agreement: −1.83 to 2.00) and the mean absolute difference was 1.24 cm. The ICC between the two methods was 0.81 (95% CI, 0.58–0.92). Conclusions Assessment and measurement of cervical dilatation by 2D transperineal ultrasound is feasible, with close agreement shown between the technique and digital vaginal examination. The technique that we describe could represent an important component of a 'sonopartogram' for ultrasound assessment of labor progress. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.